Ultra‐performance LC Separation and Quadrupole Time‐of‐flight MS Identification of Major Alkaloids in Plumula Nelumbinis. Issue 6 (14th April 2014) - Lin, Zongtao; Yang, Ruinan; Guan, Zheng; Chen, Ailiang; Li, Wei
ABSTRACT Introduction As an essential medicine and tea source in many countries, Plumula Nelumbinis potentially exerts its major biological activities through its alkaloids. However, the activities of Plumula Nelumbinis are not fully understood due to the lack of studies on its chemical components. Objective To establish an ultra‐performance liquid chromatography combined with diode‐array detector (UPLC/DAD) method, coupled to an electrospray ionisation with quadrupole time‐of‐flight mass spectrometry (ESI/QTOF/MS) method, for the separation and identification of Plumula Nelumbinis alkaloids. Methods The eluant from an UPLC separation of an ethanol extract of Plumula Nelumbinis was directly infused into an ESI/QTOF/MS system. Both positive and negative ion modes of ESI with low and high collision energy (CE) were used to obtain sufficient MS information. Results Twenty‐one alkaloids were tentatively identified based on their chromatographic characteristics, UV spectra, exact mass, MS fragments and literature reports. They consist of six bis‐1‐benzyltetrahydroisoquinoline, eleven benzyltetrahydroisoquinoline (including two glycoalkaloids and two quaternary ammoniums), two aporphine, one proaporphine and one indole alkaloids. Eleven were identified in Plumula Nelumbinis for the first time and seven were first reported in Nelumbo nucifera Gaertn. Five compounds, namely norcoclaurine‐4′‐O‐glucoside, norcoclaurine‐6‐O‐glucoside, isolotusine, 6‐demethyl‐4‐demethylN‐methylcoclaurine and N‐norisoliensinine, were characterised and proposed as new compounds. Conclusion The established UPLC/DAD − ESI/QTOF/MS method is efficient for systematic identification of the alkaloids in Plumula Nelumbinis extract. Copyright © 2014 John Wiley & Sons, Ltd.